Gel Formulation and Evaluation Of Cassava (Manihot esculenta) Flour As Accoustic Coupling Agent (ACA) Ultrasonography - Romadhoni, Efriza Nur; Putri, Maizza Nadia; Hanifan, Arinal Hanifan; Fajriyah, Ayu Yuliana; Lokatara, Sista Lokatara; Wibowo, Gatot Murti (Postgraduate Program , Poltekkes Kemenkes Semarang, 2022)
Background: World consumption of hydrogels from synthetic polymers is more than one million tons per year (El Mohdi, 2009). This can cause serious environmental damage problems. According to Moorthy (2004), the amylose content of tapioca flour is in the range of 20-27%. Cassava has a high amylopectin content, with the addition of aloe vera, it is hoped that the gel will be safer and better for patients with sensitive skin problems (Jahan, 2020).Methods: Experimental with true experimental design using posttest only control group design.Results: Three different gel formulations were obtained, including A2 gel with a composition of 25 grams of cassava flour, 4 grams of aloe vera gel, 0.1 grams of methyl paraben and 75 mL of distilled water. Gel B2 with a composition of 25 grams of cassava flour, 4 grams of aloe vera gel, 0.1 grams of methyl paraben, 100 mL of distilled water. The composition of the C2 gel includes 25 grams of cassava flour, 4 grams of aloe vera gel, 0.1 grams of methyl paraben and 125 mL of distilled water. Gel A2 has a standard pH and spreadability.Conclusion: The results of the evaluation of the formula have shown conformity with the parameters set so that gel A2 was chosen to be the optimum formula. Keyword : Cassava, Gel, Ultrasonography.